Hematological parameters of the suri (Rhea pennata) in conditions of captivity in the Peruvian high plateau - Valeriano-Pari, Vitaliano (2019)
The aim of this study was to evaluate the hematological constants of the red and white series in suri (Rhea pennata) in captivity in the Peruvian high plateau, considering, in addition, the sex and age variables. Sampling was done on 28 individuals from the Lupaca Rescue Center, El Collao province, Puno region, Peru, at 4530 m. The birds were 14 females and 14 males, corresponding to seven juveniles (12-23 months) and seven adults (more than 24 months) in each case. The animals were apparently healthy. The blood samples were obtained after fasting in the morning by puncture in the axillary vein. The count of erythrocytes and leukocytes was determined using the Neubauer hemocytometer, the Natt-Herrick solution and blood smear stained with the Wrigth stain, hematocrit by microhematocrit, and hemoglobin by spectrophotometry using the cyanometahemoglobin method. The hematological values between females and males were similar. The hematocrit found in juveniles was higher in 10%, the heterophiles in more than 5% and lymphocytes in 8% with respect to adults (p<0.05), while monocytes and eosinophils were 5 and 9% higher, respectively, in adults as compared to juveniles (p<0.05).